2021
DOI: 10.1016/j.ijid.2021.02.102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and socio-environmental determinants of multidrug-resistant vibrio cholerae 01 in older children and adults in Bangladesh

Abstract: Few studies have evaluated determinants of multidrug-resistant (MDR) Vibrio cholerae O1 in older children and adults. This study aimed to characterize the prevalence of MDR V. cholerae O1 and associated risk factors among patients over five years of age in Bangladesh. Methods: Stool culture and antimicrobial susceptibility testing were performed as a part of a larger study at Dhaka Hospital in Bangladesh from March 2019-March 2020. Univariate statistics and multiple logistic regression were used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
10
2
Order By: Relevance
“…For example, tetracycline (TE) was the priority drug widely used for the treatment of cholera, but its clinical use was reduced drastically because of the emergence of TE resistant V. cholerae strains in Asia and Africa (5). The recently isolated V. cholerae O1 strains in South Asia, including Bangladesh, were found to be susceptible against TE (35)(36)(37). In the present study all of the V. cholerae isolates tested were susceptible towards TE.…”
Section: Discussionmentioning
confidence: 59%
“…For example, tetracycline (TE) was the priority drug widely used for the treatment of cholera, but its clinical use was reduced drastically because of the emergence of TE resistant V. cholerae strains in Asia and Africa (5). The recently isolated V. cholerae O1 strains in South Asia, including Bangladesh, were found to be susceptible against TE (35)(36)(37). In the present study all of the V. cholerae isolates tested were susceptible towards TE.…”
Section: Discussionmentioning
confidence: 59%
“…For example, tetracycline (TE) was the priority drug widely used for the treatment of cholera, but its clinical use was reduced drastically because of the emergence of TE resistant V. cholerae strains in Asia and Africa [ 5 ]. The recently isolated V. cholerae O1 strains in South Asia, including Bangladesh, were found to be susceptible against TE [ 40 42 ]. In the present study all of the V. cholerae isolates tested were susceptible towards TE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the resistance is due to mutation in the chromosome and/or acquisition of mobile genetic elements such as plasmids, transposons, and integrating conjugative elements. 26,27 AMR in cholera leads to an increase in healthcare costs, morbidities, mortalities, and prolonged hospitalization. 3 Antimicrobial multidrug resistance is most common among the atypical cholera strains, which is associated with the acquirement of genes and/or modification in the antibiotic target.…”
Section: Antimicrobial Resistance In Choleramentioning
confidence: 99%
“…2 In Nigeria, high resistance in tetracycline and ampicillin 3 were reported, in contrast, to 3 Stephanie et al reported that the O1 cholera strain is highly sensitive to tetracycline in Bangladesh. 26 Resistance to antimicrobial among V. cholerae O1 varies considerably between regions and over time. 28 Garbati et al reported that amikacin, cefotaxime, and ciprofloxacin are sensitive, while tetracycline, trimethoprim/sulfamethoxazole are resistant.…”
Section: Antimicrobial Resistance In Choleramentioning
confidence: 99%